MEMBUMIKAN TEOLOGI ISLAM DALAM KEHIDUPAN BERAGAMA (PERSPEKTIF M ARKOUN) - Zulkarnain Zulkarnain (UIN Sumatera Utara Medan, 2023)
Point inertia classical Islamic theology thought would appear in the realm of reality if the thought process faced with the reality or the reality of empirical social human life is always growing and developing in line with the growth of science and technology. Mohammed Arkoun is Algerian intellectuals who tried to reread the building of Islamic thought in comprehensive both involving thought kalam (theology), Sufism, jurisprudence, ethics and interpretation. In the Indonesian context, Arkoun thought first recognized in 1987 in a discussion on Empathy Foundation. Muhammad Nasir Tamara, who introduced first by writing an article entitled Mohammed Arkoun and Applied Islamology. In some writings about modernity, Arkoun does not explicitly formulate the constraints of modernity, let alone challenge under him. According to Arkoun, modernity can be divided into two groups, namely, modernity